2015
DOI: 10.14295/bds.2015.v18i4.1172
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of the bond interface associated with nd:yag laser

Abstract: <p class="western" lang="en-US"><span style="font-family: Arial, sans-serif;"><strong>ABSTRACT</strong></span></p><p class="western" align="justify"><span style="color: #000000;"><span style="font-family: Arial, sans-serif;"><span lang="en-US"><strong>Objective</strong></span></span></span><span style="color: #000000;"><span style="font-family: Arial, sans-serif;"><span lang="en-US">:This study evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…In addition, the presence of MDP and NaF in the Clearfil Liner Bond F may have contributed to the increased bond strength. Barcellos et al [27] found laser irradiation to increase the modulus of elasticity of the formed hybrid layer, causing less polymerization shrinkage stresses at the interface. This may explain the intact hybrid layer seen in group TS-L.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the presence of MDP and NaF in the Clearfil Liner Bond F may have contributed to the increased bond strength. Barcellos et al [27] found laser irradiation to increase the modulus of elasticity of the formed hybrid layer, causing less polymerization shrinkage stresses at the interface. This may explain the intact hybrid layer seen in group TS-L.…”
Section: Discussionmentioning
confidence: 99%
“…The authors theorized that the heat energy from the laser formed a new substrate in which the hydroxyapatite has been melted and fused in the presence of bond monomers. [23] The use of laser energy on the bonding agent before its curing has since been evaluated in further studies and has been further hypothesized to increase bond penetration [24], help evaporate the solvent [25], increase its degree of conversion (DC) [26], and increase the modulus of elasticity of the hybrid layer [27]. All supposedly through the photothermal effect of the laser on the adhesive.…”
Section: Introductionmentioning
confidence: 99%